Discovery of face-centred cubic Os nanoparticles. Issue 3 (6th December 2019) - Wakisaka, Takuo; Kusada, Kohei; Yamamoto, Tomokazu; Toriyama, Takaaki; Matsumura, Syo; Ibrahima, Gueye; Seo, Okkyun; Kim, Jaemyung; Hiroi, Satoshi; Sakata, Osami; Kawaguchi, Shogo; Kubota, Yoshiki; et al.
Abstract : The first example of the crystal structure control of Os is reported. The fcc-structured Os nanoparticles were synthesized using an Os acetylacetonate complex as a precursor although the fcc structure does not exist in the bulk state. Abstract : We succeeded in controlling the crystal structure of osmium (Os) nanoparticles (NPs). Although Os adopts only a hexagonal close-packed (hcp) structure in the bulk state, a face-centred cubic (fcc) Os was synthesized by a chemical reduction method using an Os acetylacetonate complex as a precursor.